(untitled) (Journal of University of Babylon for Engineering Sciences, 2023)
The market for implant alloys, particularly those designed for orthopedic implants has expanded rapidly during the last decade. The medical sector has benefited greatly from the significant advances achieved in the study of Mg-based biodegradable alloy during this time. Research is a step up in this area for a number of reasons, including the desire to improving people quality of life (a social as well as an economic driver). By decreasing the prevalence of permanent metallic implants (such as those made of stainless steel, cobalt-based alloys, and titanium alloys), which have their own set of drawbacks (including stress shielding and metal ion releases) that can have a negative impact on patients’ mental and physical health. Biodegradable Mg alloys are discussed in this paper, along with their history of development, important features that make them desirable for such applications (orthopedic implants), and features that must be modulated (corrosion rate and mechanical properties) to arrive at the optimal product for the intended application. It emphasizes the electrochemical characterization techniques/methods and strategies to enhance the corrosion behavior and mechanical characteristics of various kinds of biodegradable alloys, as well as the mechanism and features linked to the corrosion behavior of Mg alloys. The criteria to be design, the requirements that implants of biodegradable alloys Mg-based must fulfill, and the features connected to their efficiency provided, as well as the methods of optimization, the category, and the influence of the alloying components.